Empowering KWT Mekarsari Bigaran through the ant sugar digital branding program for market expansion - Dwi Susanti; Rayinda Faizah; Prihatin Dwihantoro; Tiffani Anggi Amelia; Dessy Nurmala Sari (Community Empowerment, 2023)
The urgency of developing the Bigaran BALKONDES was expanded with the involvement of the Mekarsari Women's Farmers Group (KWT) to produce new products, one of which was Ant Sugar. Currently, KWT Mekarsari does not yet have a concept about the characteristics and advantages of Ismi ant sugar products and there are no plans for a market expansion program via digital platforms. The aim of this service activity is to focus on solving product production and management problems in several stages with the ultimate aim of increasing market share through digital branding and marketing. Service activities are carried out by implementing digital marketing training and social media management and organizational management training. The result of this activity is the availability of a new brand from KWT Mekarsari, namely Gula Semut Mekarsari with new packaging. Apart from that, social media is also available as a digital marketing tool via the Instagram account @gulasemut.mekarsari.